To TRIM the Immunity: From Innate to Adaptive Immunity - Yang, Wenyong; Gu, Zhiwen; Zhang, Huiyuan; Hu, Hongbo (Frontiers in Immunology, 2020)
The tripartite motif (TRIM) proteins have been intensively studied as essential modulators in various biological processes, especially in regulating a wide range of signaling pathways involved in immune responses. Most TRIM proteins have E3 ubiquitin ligase activity, mediating the polyubiquitination of target proteins. Emerging evidence has demonstrated that TRIM proteins function in innate immunity by regulating pattern recognition receptors, vital adaptor proteins, kinases, and transcription factors in innate immune signaling pathways. Additionally, the critical roles of TRIM proteins in adaptive immunity, especially in T cell development and activation, are increasingly appreciated. In this review, we aim to summarize the studies on TRIMs in both innate and adaptive immunity, focusing on their E3 ubiquitin ligase functions in pattern recognition receptor signaling pathways and T cell functions, shedding the lights into the developing new strategies for modulating innate and adaptive immune response against invading pathogens and avoiding autoimmunity.